Rapid and Sensitive Identification of Glycoprotein H Genotypes in Clinical Human Cytomegalovirus Samples - Li, Wei; Tao, Ran; Zhang, Xiao; Shu, Qiang; Gao, Hui-Hui; Shang, Shi-Qiang; Peng, Zhao-Yang; Li, Hua-Mei (Japanese Journal of Infectious Diseases, 2015)
Human cytomegalovirus (HCMV) is a common pathogen that causes persistent infections in immune deficient patients and results in significant morbidity and mortality, particularly among transplant recipients and children. Different HCMV glycoprotein H (gH) genotypes may cause different diseases and affect the severity of these diseases. To develop a sensitive quantitative real-time PCR assay that could rapidly distinguish between two HCMV gH genotypes, primers were designed to target the conserved region of the gH gene. gH1 and gH2 probes were designed to target the two variable regions. Standard HCMV strains (AD169 and TOWNE) and 203 clinical urine samples from HCMV infected children were used for the present study. Based on the primer-probe set used to detect the target gH gene segment of HCMV, our quantitative real-time PCR assay specifically discriminated between HCMV gH1 and gH2 with a detection limit of approximately 102 viral copies/ml. Among the 203 clinical urine samples tested, 145 were gH1 positive, 56 were gH2 positive, and 2 were positive for both. Thus, we developed a gH gene-based real time-PCR method that could rapidly, stably, and specifically distinguish between two HCMV gH genotypes. We found HCMV gH1 to be common among children examined in Zhejiang, China.